2017
DOI: 10.1155/2017/2385106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma Irradiation on Agromorphological Characteristics of Okra (Abelmoschus esculentus L. Moench.)

Abstract: Cultivation of okra in Ghana is challenged by low yield due to lack of improved varieties. Gamma irradiated okra seeds can generate genetic variability to improve the crop. Samples of 150 seeds, each of okra genotype, UCCC6, were irradiated with 400 Gy to 1000 Gy using cobalt 60 source at a dose rate exposure of 121.58 Gy/hr. There were 40 stands comprising single plant per stand in three replications per treatment in a randomized complete block design outlay. Seedling survival, plant height, number of leaves,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 16 publications
4
19
0
1
Order By: Relevance
“…Based on the yield stability in various environments supported by agronomic characters (number of pods and seeds yield), two promising mutant lines (Biosoy-8 and Biosoy-11) had a high considerable opportunity to be released as improved high yielding soybean varieties with large seeds. These promising soybean mutant lines resulted in this study are in good agreement with previous reports to prove the strength of gamma irradiation to produce new plant varieties (Asare et al 2017;Harsanti and Yulidar 2019). The study clearly demonstrated that the agronomical traits evaluation and molecular variation of promising mutant lines could assist their identification and maximal utilization in the future.…”
Section: Morpho-agronomical Traits Variationsupporting
confidence: 92%
“…Based on the yield stability in various environments supported by agronomic characters (number of pods and seeds yield), two promising mutant lines (Biosoy-8 and Biosoy-11) had a high considerable opportunity to be released as improved high yielding soybean varieties with large seeds. These promising soybean mutant lines resulted in this study are in good agreement with previous reports to prove the strength of gamma irradiation to produce new plant varieties (Asare et al 2017;Harsanti and Yulidar 2019). The study clearly demonstrated that the agronomical traits evaluation and molecular variation of promising mutant lines could assist their identification and maximal utilization in the future.…”
Section: Morpho-agronomical Traits Variationsupporting
confidence: 92%
“…The median TCSA value of the population was 1.68 cm 2 and 4.18 cm 2 in 2014 and 2015, respectively, whereas TCSA was higher in 'Amasya' in both years (3.56 cm 2 and 5.89 cm 2 in 2014 and 2015, respectively) in comparison to others. Mutagens make plants to grow slowly, leading to a reduction in plant height (MALEK et al, 2014;GANAPATHI et al, 2015;ASARE et al, 2017). In this study, both tree height and TCSA showed marked variations among the mutants.…”
Section: Resultsmentioning
confidence: 55%
“…There might be numerous factors (such as protein synthesis, leaf gas and water exchange) affected by irradiation, which may lead the reduction in tree height (DATTA et al, 2011;LAGODA, 2012;ALI et al, 2016). Also, cell division and cell elongation stages of plants are affected negatively by irradiation (ASARE et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Gujarat Cumin-4 was obtained while the highest dose (500 Gy) resulted in minimum seed germination (9.52%) (Verma et al 2017). Also, plant height, seedling survival, stem diameter, number of leaves, leaf length, number of branches and leaf width of okra decreased significantly with increasing doses of gamma rays (Asare et al 2017). Furthermore, Singh et al (2013) stated that gamma radiation at a low dose of 25 Gy or lower stimulates, while high dose of 100 Gy and above inhibits plant growth and development of wheat cultivar PBW-343.…”
Section: Discussionmentioning
confidence: 99%